Empathy regulation, prosociality, and moral judgment. (April 2022) - Cameron, C. Daryl; Conway, Paul; Scheffer, Julian A.
Abstract: In this review, we examine relationships between empathy, prosocial behavior, and moral judgment. We focus on recent evidence for these relationships, with a focus on motivated empathy regulation as an important process that shapes empathic and moral outcomes. In particular, we highlight tradeoffs in contexts that involve competing victims with different needs, such as in large-scale suffering situations and sacrificial moral dilemmas, as well as on effects on punishment and recursive effects of morality on empathy. Our aim is to integrate motivation frameworks in empathy regulation and social cognition with prosocial and moral judgments. Highlights: Both experience sharing and compassion can influence prosociality and moral judgment. A motivational approach suggests people balance costs and rewards of empathy. Compassion's collapse towards mass suffering can depend on anticipated rewards and costs. The effect of empathy in sacrificial dilemmas is complex and depends on focal targets. Likewise, empathy can increase or reduce punishment depending on focal targets. Integrating reciprocal influences of empathy and moralization can clarify empathy's link with prosociality.